LAMA2 variants associated with muscular dystrophy, brain structural abnormalities, and epilepsy: a genotype-phenotype study - Zha, Jian; Yu, Ying; Cao, Fangfang; Yi, Zhaoshi; Wu, Huaping; Chen, Yong; Zhong, Jianmin; Yu, Xiongying (Frontiers in Neurology, 2026)
BackgroundLAMA2-related congenital muscular dystrophy (LAMA2-MD) is a genetically heterogeneous disorder defined by progressive muscle weakness, brain structural abnormalities, epilepsy, and multisystem involvement. The primary goal of this study was to characterize the clinical features, temporal progression, and genotype-phenotype correlations of LAMA2-MD.MethodsMedical records of patients with genetically confirmed LAMA2-MD were extracted from a clinical data repository and analyzed retrospectively. Clinical manifestations, laboratory findings, and neuroimaging features were systematically reviewed and compared across different age groups. Variant data were retrieved from public databases to perform comprehensive genetic analyses.ResultsA total of five patients (two males and three females) were enrolled, delayed motor milestones and varying degrees of ankle contractures and persistent motor impairment in all patients were the initial presenting symptom at diagnosis in all cases, and two patients also exhibited cognitive delays. Laboratory analysis of muscle enzymes showed varying degrees of abnormalities, with creatine kinase (CK) levels displaying the most significant elevation. Cranial magnetic resonance imaging (MRI) revealed symmetrical white matter abnormalities in four patients. Seizures were documented in three school-aged patients. All patients carried compound heterozygous variants in the LAMA2 gene. A literature review indicated that the most common variant types were stop-gain and missense variants: stop-gain variants were predominantly associated with complete merosin deficiency (MDC1A), whereas missense variants typically correlated with late-onset limb-girdle muscular dystrophy.ConclusionLAMA2-MD exhibits a broad phenotypic spectrum and a progressive disease course. Early manifestations include muscle weakness, delayed achievement of developmental milestones, joint contractures, seizures and characteristic intracranial abnormalities.